CircRNF13 enhances IGF2BP1 phase separation-mediated ITGB1 mRNA stabilization in an m6A-dependent manner to promote oral cancer cisplatin chemoresistance - Xuemeng Xu; Qiu Peng; Zongyao Ren; Yaqian Han; Xianjie Jiang; Zhu Wu; Shiming Tan; Wenjuan Yang; Linda Oyang; Xia Luo; Jinguan Lin; Longzheng Xia; et al. (Molecular Cancer)
Abstract Oral cancer ranks among the most common malignancies within the head and neck region; however, its etiology remains inadequately understood despite substantial research advances in recent years. Many studies highlight the regulatory role of circular RNAs (circRNAs) in human cancers, suggesting their potential as cancer biomarkers. However, their specific mechanisms in oral cancer are not well understood. This study analyzed circRNAs expression in oral cancer, identifying circRNF13 (circbaseID: has_circ_0006801) as having elevated expression in oral cancer cells and tissues. Our study demonstrated that circRNF13 is correlated with increased tumor grade and stage in oral cancer. Results from both in vitro and in vivo experiments indicated that circRNF13 enhances cancer cell proliferation and tumor growth, while concurrently diminishing tumor sensitivity to cisplatin. Mechanistically, circRNF13 interacts with the m6A “reader” protein IGF2BP1, inhibiting its ubiquitin-mediated degradation and promoting its phase separation formation. Subsequently, circRNF13 augments the stability of ITGB1 mRNA via IGF2BP1 in a manner dependent on m6A modification. The m6A modification of ITGB1 mRNA is modulated by the phase separation of IGF2BP1, thereby promoting the malignant progression of oral cancer cells. This evidence positions circRNF13 as a crucial regulatory molecule in the pathogenesis of oral cancer and suggests its potential as a therapeutic target. This discovery enriches our understanding of the mechanistic role of circRNAs.